Analysis of the recoverable glucose content of Chaetoceros calcitrans for its potential in biothanol production. - Famisaran, Ronald Patrick A. (College of Fisheries, University of the Philippines, 2009)
This study looked into the proximate glucose content of microalgal species chaetoceros calcitrans subjected to 3 different treatments. Samples of C. calcitrans were cultured for 3 days in 1L and scaled up in 5L volume in the duration of 5 days. Enrichment media and fertilizers used for culture are F medium (treatment 1), 16-20-30 (treatment 2), and 14-14-14 (treatment 3). Samples were then pretreated by hydrolysis for analysis of its sugar content using a method described by dubois et al (1956). Highest glucose concentration accounted is from the sample treated with 16-20-0 fertilizezrs at 19.3 mg/1 but revealed no significant difference (p<0.01) as compared to other glucose concentration accumulated form the other treatments (F medium and 14-14-14). Growth rates of c. calcitrans under different nutrient enrichment were also measured with highest growth rate displayed by sample treated with F medium. Glucose yield from the microalgal species from a 1-hectare pond at 1 m depth was also projected using dry weight of the algal biomass. Results showed that highest yield of glucose can be attained from the sample subjected to F medium at 2,728.35 kg.